Investigation of photocatalytic properties of TiO2 nanoparticle coating on fly ash and red mud based porous ceramic substrate - Ozcan, Mucahid; Birol, Burak; Kaya, Figen (ELSEVIER SCI LTD, 2021)
Titanium dioxide is one of the best semiconducting photocatalysts available for photocatalytic cleaning applications. Especially nano-sized TiO2 particles deposited on porous substrates can be utilized as a filter for solid and liquid media. On the other hand, red mud and thermal plant fly ash are hazardous wastes that are produced in large quantities. Recycling/reuse of these waste material in a porous ceramic production would be beneficial both for environmental and economical issues. In the present study, a porous substrate was produced from red mud and fly ash with varying ratios and additives of H3BO3, CaCO3, and MgCO3 for lowering the melting temperature and porosity formation. Sintered ceramics were then coated with nano-sized TiO2 particles by the sol-gel method. Ultrasonic dispersion of nano-sized TiO2 nanoparticles was also utilized as an alternative method for impregnation of nanoparticles into the porous structure of the ceramic substrate. Finally, photocatalytic activities and degradation of methylene blue (MB) under UV radiation of substrates were investigated. According to the SEM investigations, the sol-gel method was observed to be a better way of nanoparticle deposition because deposited particles are homogenous throughout the ceramic body. Also, this method provides lower particle sizes than the ones that were deposited by the ultrasonic dispersion method. This results in higher surface area and better photocatalytic activities.
Keywords: Porous ceramics; Fly ash; Red mud; Coating; TiO2 nanoparticles; AQUEOUS-SOLUTION; FOAM; CLAY; GLASS; DEGRADATION; INDUSTRY; REMOVAL; Materials Science